Transfiksyon mga kathang in-transit - Tolentino, Rolando B.; Rodriguez, Rommel B. (Quezon City University of the Philippines Press, 2014)
Collection of modern Tagalog fiction.
In Tagalog.
Includes bibliographical references (page xxviii).
Keywords: Short stories, Tagalog; Short stories, Filipino; Tagalog fiction